2016
DOI: 10.1002/ptr.5601
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylethanolamide Exerts Antiproliferative Effect and Downregulates VEGF Signaling in Caco-2 Human Colon Carcinoma Cell Line Through a Selective PPAR-α-Dependent Inhibition of Akt/mTOR Pathway

Abstract: Palmitoylethanolamide (PEA) is a nutraceutical compound that has been demonstrated to improve intestinal inflammation. We aimed at evaluating its antiproliferative and antiangiogenic effects in human colon adenocarcinoma Caco-2 cell line. Caco-2 cells were treated with increasing concentrations of PEA (0.001, 0.01 and 0.1 μM) in the presence of peroxisome proliferator-activated receptor-a (PPAR-α) or PPAR-γ antagonists. Cell proliferation was evaluated by performing a MTT assay. Vascular endothelial growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…The enteroprotective effect of PEA passes through the direct or indirect activation of PPAR-α and CB2 receptors [138][139][140][144][145][146][147], whose expression has also been confirmed in the canine and feline gastrointestinal tract [101,109]. It has also recently been found that PEA restores the intestinal barrier permeability via the regulation of intercellular junctions [139,146,[148][149][150], and reduces inflammatory cell recruitment, i.e., macrophages and neutrophils, during experimental intestinal injury [138,144,147,[151][152][153][154]. PEA administration also decreased viral-induced diarrhea [140] and normalized intestinal motility in a post-inflammatory accelerated transit model [145].…”
Section: Gastrointestinal Tractmentioning
confidence: 92%
“…The enteroprotective effect of PEA passes through the direct or indirect activation of PPAR-α and CB2 receptors [138][139][140][144][145][146][147], whose expression has also been confirmed in the canine and feline gastrointestinal tract [101,109]. It has also recently been found that PEA restores the intestinal barrier permeability via the regulation of intercellular junctions [139,146,[148][149][150], and reduces inflammatory cell recruitment, i.e., macrophages and neutrophils, during experimental intestinal injury [138,144,147,[151][152][153][154]. PEA administration also decreased viral-induced diarrhea [140] and normalized intestinal motility in a post-inflammatory accelerated transit model [145].…”
Section: Gastrointestinal Tractmentioning
confidence: 92%
“…PEA exerts potent anti-inflammatory effects, and it has been shown to improve intestinal inflammation, following both intraperitoneal and oral administration [ 5 ], in animal models of colitis. More importantly, its efficacy has also been demonstrated in mucosal biopsies from patients with ulcerative colitis (UC) [ 6 , 7 , 8 ], with the peroxisome proliferator activated receptor α (PPARα) being one of the key receptors mediating these effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its pivotal role in hypoxia-mediated radioresistance, HIF-1α promotes tumor recurrence after RT by increasing tumor repopulation and protecting tumor blood vascular structure via VEGF production [34,47]. Indeed, the mTOR signaling pathway not only increases HIF-1α synthesis, but also promotes tumor angiogenesis in CRC cells [48,49,50]. In this study, we observed that BEZ235 and RT treatments followed by BEZ235 maintenance treatment significantly downregulated VEGF-A and HIF-1α expression in CRC cell lines and xenograft tumor tissue.…”
Section: Discussionmentioning
confidence: 99%